Progress of Learning in Secondary Education of Argentina: A Multinivel Analysis of Added Value - Ruben Cervini (Universidad Autónoma de Madrid, 2018)
Pupils in schools of 44 districts in the Buenos Aires state of Argentina were test twice (grade 7 in 2001 and grade 9 in 2003) on their proficiency in language (Spanish) and mathematic. Based on 6,133 students in 96 schools for Math and 6,862 students in 97 schools for language, the major objectives of this study are (i) to assess the educational progress of pupils between those years, (ii) to detect whether between schools differences in progress scores on both subjects ('value added') exist and (iii) to what extent those differences can be explained by both background student and group 'composition' variables. The results of multilevel analyses indicate that differences between schools were no more significant when account was taken of those both type of variables. Gils made more progress than boys in language and less in mathematic. Socioeconomic status indicators are relevant predictors of both mathematic and language student progress. After controlling for backgrounds student characteristics, the (intellectual and socioeconomic) group composition at the school level remained very important for the explanation of the differences in both subjects. Pupils made on average more progress in schools with higher levels of intellectual and/or socioeconomic composition. As a consequence, no strong evidences of differential effectiveness of school were found.